The Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on their Destruction: History of Signing and Key Points - V. N. Fateenkov (Вестник войск РХБ защиты)
The Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on their Destruction (the Chemical Weapons Convention or CWC) was approved by the U.N. General Assembly on 30 November 1992. The treaty entered into force on 29 April 1997. The aim of this work was to study the history of signing of the CWC and its key points. First attempts to develop an international agreement restricting the use of poisons and various toxic substances in hostilities have been made in the 17th century, when the 1675 Strasbourg Agreement between France and the Holy Roman Empire banned the use of poisoned bullets. During the First and Second Peace Conferences in The Hague (1899 and 1907), its participants pledged to refrain from employing «poison or poisoned arms» and from employing «arms, projectiles, or material of a nature to cause superfluous injury». The First World War showed that this ban turned out to be ineffective, and chemical weapons appeared on the battlefield. After the war, the «Protocol for the Prohibition of the Use in War of Asphyxiating, Poisonous or Other Gases, and of Bacteriological Methods of Warfare», known as the Geneva Protocol of 1925, was developed. But this document did not ban the elaboration and the production of chemical weapons. The High Contracting Parties agreed not to use «asphyxiating, poisonous or other gases, and of all analogous liquids, materials or devices» against those States only, that acceded to the Protocol. Moreover, many States-Parties reserved their right to use chemical weapons in response to a first use by an enemy. The Iran-Iraq War (1980–1988) showed the ineffectiveness of the Geneva Protocol of 1925. Iraq’s massive use of chemical weapons against Iranian troops has accelerated the process of developing an international document – the CWC, the world`s first multilateral disarmament agreement, which provided for the verifiable elimination, within the prescribed time limit, of an entire class of weapons of mass destruction – chemical weapons. Nowadays 192 states have become parties to the CWC. The Russian Federation fully complied with the obligations undertaken by the CWC, the last Russian chemical munition was destroyed in September 2017.